An Experimental Study on the Role of Narrative Text in Enhancing Student Motivation in Reading Comprehension - Hamzah, Arfah; Rauf, Wahyuddin; Zia Ul Haq , Muhammad; Muhammad Nur , Andi (Jurnal Edukasi Saintifik, 2025)
This study investigates the effectiveness of using narrative texts to enhance student motivation and reading comprehension in English learning among XI IPA 1 students at MAN 1 Barru during the 2023/2024 academic year. Employing a one-group pretest and post-test design, this quantitative research systematically collects and analyzes numerical data to measure student progress. The findings reveal a significant improvement in students’ reading comprehension, as indicated by an increase in the mean score from 69.00 in the pre-test to 87.00 in the post-test. Additionally, the number of students achieving the mastery threshold (≥75) rose from 16.0% (4 students) in the pre-test to 48.0% (12 students) in the post-test. Statistical analysis confirmed that this improvement was highly significant (p = 0.000). These results indicate that learning with narrative texts effectively enhances students' reading comprehension skills, contributing to their overall English language proficiency. The findings of this study confirm that the implementation of narrative texts in reading instruction significantly improves students’ comprehension abilities. The substantial increase in post-test scores suggests that narrative texts can serve as an effective pedagogical approach to foster motivation and engagement in reading activities. Educators are encouraged to integrate narrative texts into English language instruction to optimize student learning outcomes.